Cohort study of electroencephalography markers of amyloid-tau-neurodegeneration pathology. Issue 2 (15th July 2020) - Tanabe, Sean; Bo, Amber; White, Marissa; Parker, Margaret; Farahbakhsh, Zahra; Ballweg, Tyler; Casey, Cameron; Betthauser, Tobey; Zetterberg, Henrik; Blennow, Kaj; Christian, Brad; Bendlin, Barbara B; et al.
Abstract: Electroencephalography signatures of amyloid-β, tau and neurodegenerative pathologies would aid in screening for, tracking progression of, and critically, understanding the pathogenesis of dementia. We hypothesized that slowing of the alpha peak frequency, as a signature of hyperpolarization-activated cyclic nucleotide gated 'pacemaker' channel activity, would correlate with amyloid and tau pathology burden measured by amyloid (Pittsburgh Compound B) and tau (MK-6240) positron emission tomography or CSF biomarkers. We also hypothesized that EEG power would be associated with neurodegeneration (CSF neurofilament light and hippocampal volume). Wakeful high-density EEG data were collected from 53 subjects. Both amyloid-β and tau pathology were associated with slowing in the alpha peak frequency [Pittsburgh Compound B (+) vs. Pittsburgh Compound B (−) subjects, P  = 0.039 and MK-6240 (+) vs. MK-6240 (−) subjects, P  = 0.019]. Furthermore, slowing in the peak alpha frequency correlated with CSF Aβ42/40 ratio ( r 2 = 0.270; P  = 0.003), phosphoTau (pTau181, r 2 = 0.290; P  = 0.001) and pTau181 /Aβ42 ( r 2 = 0.343; P  < 0.001). Alpha peak frequency was not associated with neurodegeneration. Higher CSF neurofilament light was associated with lower total EEG power ( r 2 = 0.136; P  = 0.018), theta power ( r 2 = 0.148; P  = 0.014) and beta power ( r 2 = 0.216; P  = 0.002); the latter was also associated with normalized hippocampal volume ( r 2 = 0.196; P  = 0.002). Amyloid-tau and neurodegenerative pathologies are associated with distinct electrophysiological signatures that may be useful as mechanistic tools and diagnostic/treatment effect biomarkers in clinical trials. Abstract : EEG signatures of amyloid-β, tau, and neurodegenerative pathologies would aid in the understanding the pathogenesis of dementia. Both amyloid-β and tau pathology were associated with slowing in the alpha peak frequency while neurodegeneration was associated with lower EEG power. Graphical Abstract: